Anxious child: the association between helicopter parenting and anxiety among primary school students in Kedah, Malaysia - Charles Ganaprakasam; Humayra, Syeda; Kalaivani Ganasegaran; Hanif Asyraf Hashim; Selvamalar Armathlingam (Penerbit Universiti Kebangsaan Malaysia, 2023)
Anxiety disorder is prevalent among children and can be accounted to multiple factors, including parenting practice. However, there is a paucity of empirical evidence on the underlying mechanism and efficacy of a screening tool that can be utilized for anxiety assessment purposes, particularly among children. Therefore, this study investigates the reliability and factorial structure of the Screen for Child Anxiety Related Emotional Disorders (SCARED) instrument and its association with helicopter parenting among primary school students. The online cross-sectional study consisted of 181 respondents selected through convenience sampling. The questionnaire was distributed through the WhatsApp messaging application with the assistance of school counselors. The findings indicated that 109 participants (60.2%) indicated the presence of anxiety disorder. Meanwhile, the factorial analysis demonstrated that the five-factor structure model of SCARED had a good model fit in this population with a total of 41.8% variances. A significant association was also found between helicopter parenting and Social Anxiety Disorder (SAD), Significant School Avoidance (SH), Generalized Anxiety Disorder (GAD), Panic Disorder (PN), and Separation Anxiety (SA). Such findings imply that SCARED is indeed reliable in measuring anxiety symptoms among children and highlight the critical role of parenting in nurturing socially functional individuals.